Digital Health Literacy and Its Role in Promoting Health Lifestyle Behaviors Among University Student: A Literature Study - Libi Bewijsshodaa; Esti Novi Andyarini (International Conference on Sustainable Health Promotion, 2025)
The development of digital technology has changed the pattern of access to health information, especially among students who live as digital natives. This situation requires Digital Health Literacy (DHL) so that students are able to sort through information, avoid exposure to hoaxes, and adapt a healthy lifestyle. This study aims to examine the role of DHL in three main dimensions such as strengthening students’ critical abilities to evaluate health information, the role of DHL to reduce the spread of hoaxes through education-based literacy practices, and its contribution to encourage the implementation of healthy lifestyles. The study is based on a literature study method, drawing on scientific sources from 2019 to 2025 that were relevant to the research theme. The findings suggest that students with high DHL levels tend to stick consistently to healthy habits, more selective before sharing health-related content, and demonstrate sharper to think critically, thereby contributing to both academic quality and health. In short, DHL is not only a technical skill, but also intellectual and social capital that shapes the digital health ecosystem on campus. Future studies are recommended to included empirical research across diverse socio-cultural contexts to deepen the understanding of DHL’s role.